3D printing of Aluminium alloys: Additive Manufacturing of Aluminium alloys using selective laser melting. (December 2019) - Aboulkhair, Nesma T.; Simonelli, Marco; Parry, Luke; Ashcroft, Ian; Tuck, Christopher; Hague, Richard
Abstract: Metal Additive Manufacturing (AM) processes, such as selective laser melting (SLM), enable the fabrication of arbitrary 3D-structures with unprecedented degrees of freedom. Research is rapidly progressing in this field, with promising results opening up a range of possible applications across both scientific and industrial sectors. Many sectors are now benefiting from fabricating complex structures using AM technologies to achieve the objectives of light-weighting, increased functionality, and part number reduction, among others. AM also lends potential in fulfilling demands for reducing the cost and design-to-manufacture time. Aluminium alloys are of the main material systems receiving attention in SLM research, being favoured in many high-value applications. However, processing them is challenging due to the difficulties associated with laser-melting aluminium where parts suffer various defects. A number of studies in recent years have developed approaches to remedy them and reported successful SLM of various Al-alloys and have gone on to explore its potential application in advanced componentry. This paper reports on recent advancements in this area and highlights some key topics requiring attention for further progression. It aims to develop a comprehensive understanding of the interrelation between the various aspects of the subject, as this is essential to demonstrate credibility for industrial needs.